The Cold War and its legacy in Indonesia - Mayasari-Hoffert, Silvia, author.
1 online resource.
Keywords: "Mayasari-Hoffert examines the depiction of the Left in Indonesian literature since the anti-leftist purge in 1965. With close textual analysis of Indonesian literary texts and their political context, this book investigates how the New Order regime under Suharto was able to build a metanarrative of liberation while purging the Left in Indonesia. Even after the regime's end in 1998, many Indonesians still have an ingrained fear of the prospect of Communism, with the result being that literary representation of the Left is still seen as problematic. Through reviewing Indonesia's institution of literature, the use and abuse of universal humanism under the New Order regime is examined, and the ways in which power intersects with literature is explored. An informative read for scholars and students of Indonesian politics, literature, and the cultural cold war"--